2018
DOI: 10.1519/jsc.0000000000001984
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two Combined Exercise Designs Associated With High-Fat Meal Consumption on Postprandial Lipemia, Insulinemia, and Oxidative Stress

Abstract: Farinha, JB, Macedo, CEO, Rodrigues-Krause, J, Krüger, RL, Boeno, FP, Macedo, RCO, Queiroz, JN, Teixeira, BC, and Reischak-Oliveira, A. Effects of two combined exercise designs associated with high-fat meal consumption on postprandial lipemia, insulinemia, and oxidative stress. J Strength Cond Res 32(5): 1422-1430, 2018-Impaired postprandial lipemia (PPL) response after the consumption of a high-fat meal (HFM) is linked to diabetes, oxidative stress, and cardiovascular events. The aim of this study was to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 25 publications
0
11
0
2
Order By: Relevance
“…Although resistance exercise alone has been shown to attenuate postprandial lipemia (32,38), more attention is needed in the area of acute resistance exercise and postprandial OS. Recently, Farinha et al (10) reported that acutely performing strength and running exercises attenuates postprandial lipemia; it is, however, not clear if resistance exercise alone can achieve similar results. Yet, based on the findings from this study (10) it seems that a resistance exercise protocol involving both the upper-body and lower-body strength exercises may be effective at lowering postprandial lipemia.…”
Section: Introductionmentioning
confidence: 99%
“…Although resistance exercise alone has been shown to attenuate postprandial lipemia (32,38), more attention is needed in the area of acute resistance exercise and postprandial OS. Recently, Farinha et al (10) reported that acutely performing strength and running exercises attenuates postprandial lipemia; it is, however, not clear if resistance exercise alone can achieve similar results. Yet, based on the findings from this study (10) it seems that a resistance exercise protocol involving both the upper-body and lower-body strength exercises may be effective at lowering postprandial lipemia.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2014, 36 studies have confirmed that exercise performed on the evening prior to a morning high-fat meal (that is, a meal containing above 0.7 g of fat per kg body mass) lowers PPL, compared to no exercise. This has been shown in young, middle-aged and/or older men [14,21,[33][34][35][36][37][38][39][40][41][42]22,43,76,77,23,[27][28][29][30][31][32], young men and women [44], young or middle-aged women [45,67], normal and overweight individuals [68], overweight and obese individuals [24,46,47] and adolescent boys and girls [48][49][50][51][52][53].…”
Section: Exercise Performed On the Day Preceding A High-fat Mealmentioning
confidence: 84%
“…TAG reduction of 22% (range 4 to 35%) [14,28,[37][38][39][40][41][42][43][44][45][46]29,[47][48][49][50][51][52][53][54][55][56]30,[57][58][59][60][61][62][63][64][65][66]31,67,68,[32][33][34][35][36]. iv.…”
Section: Accepted Manuscriptunclassified
“…Numerous studies have shown that exercise can have a beneficial effect on postprandial lipemia ( 86 88 , 105 ). Postprandial lipemia can be reduced by a single exercise ( 89 ).…”
Section: Interventions On Postprandial Lipemiamentioning
confidence: 99%